Elaboración de un plan estratégico para la Empresa “Itc Store” de la ciudad de Loja periodo 2021-2026 - Fierro Delgado, katherine Cecibel (2023)
The present thesis work entitled "DEVELOPMENT OF A STRATEGIC PLAN FOR THE COMPANY "ITC STORE" OF THE CITY OF LOJA PERIOD 2021-2026", has as its general objective "To elaborate a strategic plan for the company ITC Store of the city of Loja, period 2021-2026, to carry it out, the methods detailed below were used: Observation, in order to collect and organize information to state a hypothesis. Induction: which consists in the process of formulating the hypothesis. Deduction: It is after the field work, establish the conclusions and recommendations based on the empirical information collected. Demonstration: which consists of testing the hypothesis using empirical data. Evaluation: that evaluates and analyzes the data collected in the previous tests carried out in order to draw conclusions. For the development of the strategic diagnosis of the ITC Store microenterprise, we consider the company as an open system, where the Internal Environment and the External Environment will be taken as a reference. For which, the SWOT analysis approach is used to determine those factors that exert a positive or negative influence on the Company. Finally, it has been possible to conclude and recommend the application of suitable strategies for the ITC Store company, and in this way, it can gain a position in the local market, in order to have higher income and profits. It is concluded that the design and proposals of the plan, are tools to optimize of processes. Key words: Strategic plan, Microenterprise, Sales, Management, Administrative and accounting processes.